The age marker as a predictive indicator for frailty syndrome in the elderly - doi: 10.4025/actascihealthsci.v35i2.12489 (Acta Scientiarum. Health Sciences, 2013)
The objective of the study was to analyze the age marker in males and females as a predictor of the absence of frailty syndrome in the elderly. This was a cross-sectional study with 624 individuals. Receiver Operating Characteristic (ROC) curves were constructed and compared to areas of age, gender and absence of frailty. Cut-off points for age (years) were established to predict the absence of frailty (95% CI). The largest areas under the ROC curve for age were found for females. It was observed that the age of 72 years (women) or 67 (men) were the best cut-off points for predicting the absence of frailty. The age marker can serve as an important indicator in selecting priority groups for certain interventions.